Louis Sullivan : an American architect - Cannon, Patrick F.; Caulfield, James, 1953- (Chicago : Glessner House, 2024)
"Long considered the father of the skyscraper, Louis Henry Sullivan (1856-1924) first came to wide attention in 1889 with the completion of the Auditorium Building in Chicago. Louis Sullivan presents, for the first time, every remaining structure designed by the architect, accompanied by striking color photographs and highlights of his life and accomplishments"--
A life in architecture -- Housing a growing Chicago -- Reaching for the sky -- The wonder of the age -- Temples to God, temples to commerce -- Decline and triumph -- Fragments.
Includes bibliographical references and index.
Keywords: Sullivan, Louis H., -- 1856-1924 -- Criticism and interpretation; Architecture -- Illinois -- Chicago Region; Chicago (Ill.) -- Buildings, structures, etc; Print books